Challenges and Opportunities of Telemedicine for Women's Sexual Satisfaction: A Systematic Review. - Joneidi, Elham; Najmabadi, Khadijeh Mirzaii; Aalaei, Shokoufeh (Journal of Nursing & Midwifery Sciences, 2024)
Context: Women's sexual health is a vital component of reproductive health, and sexual satisfaction is considered a fundamental human right. Cell phone programs have emerged as tools to augment sexual knowledge, hygiene, health, and even sexually transmitted infection prevention. Objectives: This study aimed to determine the challenges and opportunities of telemedicine in improving women's sexual satisfaction. Methods: This systematic review was conducted using the newest version of the PRISMA (2020) guideline. The search was comprehensive and included Scopus, Web of Science (WOS), and PubMed databases, with no time limit until January 1, 2023. Manual reference list searches were also performed. The search strategy followed the PICO framework and included all English RCTs and quasi-experimental studies published electronically in peer-reviewed journals, which focused on using telemedicine techniques to enhance sexual satisfaction. Results: Among the selected studies, seven focused on women with various types of cancers experiencing sexual issues post-treatment. Two studies centered on women with sexual dysfunction, while one study included women without specific health concerns. Cognitive-behavioral therapy and mindfulness therapy were predominant as intervention methods. These studies identified 38 opportunities and advantages of non-attendance methods, categorized into 14 themes. Additionally, nine challenges were classified, encompassing factors such as lack of spouse participation, inadequate patient behavior follow-up, technical skill requirements, internet access, device dependency, lengthy exercises, work interference, and exercise-related embarrassment. Conclusions: This systematic review found that telemedicine's opportunity to increase access, affordability, andconvenience, along with reducing stigma, has encouraged more couples to participate. However, there are challenges, including the need for digital skills and access to technology, along with potential user discomfort with recommended exercises. Eliminating barriers is effective in optimizing telemedicine methods to increase sexual health and satisfaction.